Evaluation of outcome of pregnancy complicated by intrahepatic cholestasis of pregnancy - Sinha, Abha Rani; Kiran, Sneh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Obstetric cholestasis (OC), also known as intrahepatic cholestasis of pregnancy (ICP), is a hepatic disease unique to pregnancy which presents with intense generalized pruritus without any skin rash. The aim is to study the outcome of pregnancy both maternal and fetal complicated by OC. Methods: This retrospective case control study was conducted at the Department of Obstetrics and Gynecology, Patna Medical College and Hospital, Patna. The medical records of all women with OC who delivered between Jan 2015 and Jan 2016 were reviewed. Results: The incidence of OC was 8.2%. The most common symptom was generalized pruritus which appeared after 28 weeks in 73.3% cases. The cesarean section rate was 93.3%. A higher incidence of meconium staining in amniotic fluid at delivery (17.1% vs 1.1%, p<0.005) and preterm premature rupture of membranes (8.9% vs 1.1%, p<0.01) was noted without an increase in preterm delivery rate (24.4% vs 15.6%). There was no statistically significant difference in the following parameter - pathological cardiotocography, 1-5 minuteApgar score <7, intrauterine growth restriction, neonatal intensive care admission or perinatal mortality. There was no case of postpartum hemorrhage. Conclusions: The incidence of OC is high in the Indian population. Perinatal outcome is good in actively managed women, although at the cost of a high intervention rate.